The circular economy : case studies about the transition from the linear economy - Sillanpää, Mika E. T.; Ncibi, Mohamed Chaker (Academic Press, an imprint of Elsevier, 2019)
"The Circular Economy: Case Studies about the Transition from the Linear Economy explores examples of the circular economy in action. Unlike other books that provide narrow perceptions of wide-ranging and highly interconnected paradigms, such as supply chains, recycling, businesses models and waste management, this book provides a comprehensive overview of the circular economy from various perspectives. Its unique insights into the approaches, methods and tools that enable people to make the transformation to a circular economy show how recent research, trends and attitudes have moved beyond the "call to arms" approach to a level of maturity that requires sound scientific thinking"--Publisher's description
Keywords: Sustainable development.; Economics.; elektronické knihy; electronic books